Incentives to Identify: A Comment - Francisca M. Antman; Brian Duncan (Institute of Labor Economics (IZA), 2019)
Antman and Duncan (2014, 2015) document how racial identity responds to state affirmative action policy. The main contribution of our work was to show that racial identity responds to state affirmative action policy. A coding error was recently brought to our attention that resulted in 0.55% of our sample being misclassified in terms of their African ancestry. This paper provides details of the coding error and explores its implications. Although the error only affected a tiny percent of the overall sample, correcting it changes the conclusion of how multiracial blacks respond to state affirmative action bans, from a negative and statically significant effect to a small positive and statistically significant effect. Correcting the error does not change the conclusions for individuals with only or no African ancestry. None of the Asian ancestry classifications were affected by the coding error and thus none of the results for Asians were impacted. In addition, we present an updated analysis using more detailed ancestry classifications and more recent years of data. We continue to find that racial identity responds to state affirmative action policy, albeit with a different conclusion for multiracial blacks, and are now able to distinguish stronger effects for multiracial individuals with more distant connections to their minority group.
Keywords: J15; I28; Z13; 330; race; affirmative action; identity